Entrepreneurs’ Evaluations of Mentors: The Role of Value Similarities and Mentors’ Experiences - Kirsch, Julia; Dibbern, Rieke; Patzelt, Holger; Breugst, Nicola (Entrepreneurship education and pedagogy, 2025)
Focusing on a specific form of entrepreneurship education, entrepreneurial mentoring, we take a relational mentoring perspective and develop a model of entrepreneurs’ assessments of potential mentors. We theorize that if mentees perceive their business-related values to be similar to a potential mentor’s values, they are more likely to choose this mentor, and that this relationship is moderated by different types of the potential mentor’s experiences (i.e., entrepreneurial experience, industry experience, and mentoring experience). We test our hypotheses using a metric conjoint experiment and 2,240 assessments of potential mentors by 140 entrepreneurs. Our findings reveal that mentees' perception of business-related value similarity with a potential mentor increases the likelihood of choosing this mentor. Further, higher levels of mentors’ experiences strengthen this relationship. We discuss the implications of our study for research on entrepreneurial mentoring and relational learning in the entrepreneurial context, and we provide practical insights on how the matching process in mentoring programs may be facilitated.